(untitled) (Research, Society and Development, 2020)
The aim of this study is to observe watch-keeping duty on KM. Binaya in bad weather conditions. The method used in this study is qualitative research. This research was carried out when carrying out the sail practice for a year on KM. Binaiya and the data used were taken from several sources, second officer and crew. The result of this research shows that the use of radar navigation tools that are already good and need to be improved again and cadet on duty and the helmsman very much needs to prepare himself to help the officer on duty do the navigational watch keeping in conditions of bad weather and limited vision. Furthermore, based on the result, it can be concluded that the watch keeping cadet also plays an important role in helping the watchmaker by maximizing the use of the radar / arpa navigation tool and is more alert in reporting the dangers of the officer on duty in order to avoid collision.